Dramaturgi Pemandu Lagu Karaoke Di Kota Garut - Firmansyah; Iing Saefudin; Aam Amirudin (Program Studi Akuntansi IKOPIN, 2022)
The result of this research shows that the karaoke songstyles front stage that the karaoke songwriter in Garut city almost all play the front stage well, which is done like a glamorous, sexy and even open dress, with make-up makeup Thick and even, wearing accessories, using a formal and regular style of language, and attitude and behavior.The back stage of the karaoke songwriter in the city of Garut really plays an intact role, they do not like when on the front stage that cover their situation by actually showing the character of their self Fully naturally and more in good dynamic in the style of language, appearance and style. Impression management of karaoke songwriters in the city of Garut, they do a good impression management to achieve the desired impression in accordance with the goals that want to get by the guitarist before they play the role on the front and back stage by managing the impression such as preparing the setting, clothing , Make-up, language, style and appearance.